2009
DOI: 10.1021/np900009b
|View full text |Cite
|
Sign up to set email alerts
|

NMR Quantitation of Natural Products at the Nanomole Scale

Abstract: We describe a simple and accurate method for quantitation by solvent 13 C-satellites (QSCS), of very small amounts of natural products using microprobe NMR spectroscopy. The method takes advantage of integration of 13 C satellite peaks of deuterated solvents, in particular CDCl 3 , that have favorable intensities for measurements of samples in NMR microcoils and microprobe tubes in the 1-200 nanomole range.Recent developments in instrumentation have greatly increased the sensitivity of NMR measurements and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 20 publications
0
92
0
Order By: Relevance
“…Since NMR detects only the "soluble" fraction of AM5206 in all sample preparations, it presents a unique methodology to quantify its solubility [33][34][35]. To ensure accurate integration, we first measured the integrals of different 19 F-NMR spectra recorded using a range of recycle delays from 1 s to 30 s and confirmed that a 2 s recycle delay between scans is adequate.…”
Section: Site Selective Binding Characteristics Of Am5206mentioning
confidence: 87%
“…Since NMR detects only the "soluble" fraction of AM5206 in all sample preparations, it presents a unique methodology to quantify its solubility [33][34][35]. To ensure accurate integration, we first measured the integrals of different 19 F-NMR spectra recorded using a range of recycle delays from 1 s to 30 s and confirmed that a 2 s recycle delay between scans is adequate.…”
Section: Site Selective Binding Characteristics Of Am5206mentioning
confidence: 87%
“…In disciplines in which the available sample mass is greater, pharmaceutical sciences, medicinal chemistry, and even natural products, qNMR has been long used to qualify and quantitate samples. Advances in cryoprobe technology and the reduction of the volume of these probes have together greatly enhanced the sensitivity of NMR systems (Dalisay and Molinski, 2009;Duarte et al, 2009;Xiao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To thwart this difficulty, the residual solvent resonance has been used as an internal standard (Dalisay and Molinski, 2009;Wang et al, 2009). This concept also has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Equipment for both of these have been commercially available now for several years and when combined the resulting cryomicroprobe would give up to 15 fold increase in sensitivity compared to regular room temperature probe head (Kovacs et al, 2005). Several articles have recently been published where full NMR analyses of complex natural products have been made using only nanomoles of material (would be equal to 1 µg if molecular mass is 1000) (Dalisay & Molinski, 2009;Choi et al, 2010a;Choi et al, 2010b;Djukovic et al, 2008). If one wishes the acquisition parameters of NMR experiment can be set to provide quantitative spectrum.…”
Section: Nuclear Magnetic Resonance Spectrometry In the Metabolism Stmentioning
confidence: 99%